Suitability of wild decapods from an alluvial valley in South America for human nutrition as derived by amino acid composition - Petean, Magali; Collins, Pablo; D’Alessandro, Maria Eugenia (Elsevier, 2025)
Decapods are abundant in freshwater environments of tropical and subtropical rivers and could be considered a good resource for human feeding. The present study evaluated the nutritional quality of decapods in relation to amino acid (AA) composition and compared them with human requirements, and with the AA patterns of some crustaceans and fishes commonly consumed by human people around the world. Prawn and crab (Macrobrachium borellii and Aegla uruguayana, respectively) from the Parana River Basin were sampled. Catch effort and volume were also calculated according to the sampled area. AA was determined by high-performance liquid chromatography. Sixteen AA were identified in muscle; eight were essential amino acids for humans (EAA), and the others were non-essential amino acids (NEAA). Of the total AA, 38.0 % of those from M. borellii and 39.8 % from A. uruguayana were EAA. The NEAA values were 62.0 % for M. borellii and 60.2 % for A. uruguayana. Lipid content was close to 1 % of the biomass in wet weight in both species. When comparing decapod AA profiles with those from marine and freshwater crustacean and fishes used as food (giant river prawn, amazon river prawn, longarm river prawn, southern king crab, green tiger shrimp, speckled shrimp, tuna, sardine, hake, carp, trout, jundía catfish), the values of Leucine and Lysine in the decapods were found to be higher or equal. The amount of tyrosine in M. borellii and A. uruguayana was higher than in freshwater fishes. Nutritionally, both species are good quality food and could serve as a functional resource for the feeding of humans, nevertheless, they are not yet marketed.